A Study on Daejeon Citizens’ Perception of the Necessity for a Psychiatric Emergency Response System - Ye Won Song; 차선화 차선화; Sang-Il Kwon; Soon-Ki Ahn; Jingyu Jung; Eunji An (Korean Association of Health and Medical Sociology, 2026)
Background and Objectives: Psychiatric emergencies require immediate intervention, yet response systems and resources remain limited. Low public awareness and stigma toward mental illness may delay help-seeking and undermine the effectiveness of institutional responses. This study examined community perceptions of the need for a psychiatric emergency response system and aimed to provide evidence to inform future mental health policy. Methods: Data were obtained from the 2024 Daejeon Citizen Health Survey. The study included 2,008 adults aged 19 years or older, with sampling weights applied to reflect population distributions by sex, age, and district. Variables included awareness of psychiatric emergencies, perceived necessity of response systems, sociodemographic and mental health characteristics, and factor scores for the perceived importance of system components. Descriptive statistics, chi-square tests, t-tests, logistic regression, and multiple regression analyses were conducted using SAS version 9.4 at a significance level of 0.05. Results: Overall, 42.1% of respondents were aware of psychiatric emergencies, and the mean perceived importance score for establishing response systems was 7.77. Awareness was significantly associated with education level(elementary school or below OR=0.368, p